Ejemplo 1
Ejemplo 1
Ejemplo 1
A = cte 1 3
E = cte 2 0
L= 3 pies 3 3
lx = 1
ly = 0 1 2
1 0
k1 = AE/L 0 0
-1 0
0 0
ELEMENTO 2:
A = cte
E = cte 1 2
L= 5 pies 0.36 0.48
lx = 0.6 k2 = AE/L 0.48 0.64
ly = 0.8 -0.36 -0.48
-0.48 -0.64
1 2 3
0.40533 0.096 -0.3333
0.096 0.128 0
K= AE -0.3333 0 0.33333
0 0 0
-0.072 -0.096 0
-0.096 -0.128 0
Y
4
0
0
3 4 1 2
-1 0 1 0.33333 0
0 0 2 k1 = AE 0 0
1 0 3 -0.3333 0
0 0 4 0 0
5 6 1 2
-0.36 -0.48 1 0.072 0.096
-0.48 -0.64 2 k2 = AE 0.096 0.128
0.36 0.48 5
0.48 0.64 6
-0.072 -0.096
-0.096 -0.128
4 5 6
0 -0.072 -0.096 1
0 -0.096 -0.128 2
0 0 0 3
0 0 0 4
0 0.072 0.096 5
0 0.096 0.128 6
3 4 5 6
-0.3333 0 1
0 0 2
0.33333 0 3
0 0 4
5
6
3 4 5 6
-0.072 -0.096 1
-0.096 -0.128 2
0.072 0.096 5
0.096 0.128 6